The Academic Identity Styles Prevailing Among Hashemite University Students in Light of Was and Isaacson Scale and it is Relationship With Academic Achievement - Mahasneh, Ahmad; Al-Adamat, Omar (Jordan Journal of Educational Sciences, 2018)
This study aimed at identifying academic identity styles prevailing among Hashemite University students and its relationship to academic achievement in the light of gender and academic level. The sample consisted of (480) students who were chosen using available sampling. Academic identity styles questionnaire was used to collect data. The results of the study revealed that the achieved academic identity is the prevailing styles. In addition, the findings indicated that there were significant differences in the diffused and moratorium academic identity style that attributed to students’ gender, the level of diffused and moratorium academic identity style higher for in male than female students, and a significant differences in the achieved academic identity style attributed to students gender in favor of female students, and that there were significant differences in the diffused academic identity style that attributed to students’ gender in favor of male students, and a significant differences in the moratorium, foreclosed and achieved academic identity styles that attributed to students' academic level in favor of first, second and third years students. The result revealed that there was a positive correlation between moratorium and achieved academic identity styles and academic achievement and negative correlation between diffused academic identity styles and academic achievement